A Retrospective Review of the Use of Sirolimus for Pediatric Patients With Epithelioid Hemangioendothelioma. Issue 8 (November 2020) - Engel, Elissa R.; Cournoyer, Eily; Adams, Denise M.; Stapleton, Stacie
Abstract : Epithelioid hemangioendothelioma (EHE) is a rare malignant vascular tumor with no standardized treatment. The mammalian target of rapamycin inhibitor, sirolimus, has been used successfully in adult EHE and other vascular tumors in children but has not been studied in pediatric EHE. The aim of this retrospective case series is to discuss the results of sirolimus for treatment in 6 pediatric patients with EHE. Four of 6 patients demonstrated partial response or disease stabilization with sirolimus treatment. No treatment dosing, trough goals, or duration of treatment recommendations can be made. Prospective studies are warranted to further investigate the use of sirolimus in treatment of EHE.